Perbandingan Websocket pada Komunikasi Aplikasi Perpesanan Berbasis Android Menggunakan Library AndroidAsync, Java Websocket, dan Nv Websocket Client - Muhammad Harisuddin Thohir; Aryo Pinandito; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The growing number of mobile apps that add messaging features or even make it a key feature indicate that this feature is one of the most important features. One of the protocols that allows to be used as a two-way communication protocol is Websocket. There are several Websocket libraries that can be used, so research needs to be done to determine which is more appropriate. To be able to choose the right library then required a trial of the library. For the libraries to be tested are AndroidAsync, Java Websocket, and Nv Websocket Client. Testing is done by testing each library with several different message sizes. The results showed that the greater the message sent the speed will also be higher. As for the results of the average speed in each library shows that Nv Websocket Client is superior in terms of data transmission speed. On the other hand average power consumption results in each library shows that AndroidAsync is a library that is more efficient in the use of power when compared with other libraries.